RANCANGAN SISTEM PENGAMAN MENGGUNAKAN RASPBERRY PI DAN IP KAMERA GUNA MENINGKATKAN KEAMANAN PADA SHELTER DVOR PERUM LPPNPI CABANG MADYA YOGYAKARTA - Pradea Andika Alam; Feti Fatonah; Bambang Wijaya Putra (Politeknik Penerbangan Indonesia Curug, 2018)
The door lock system at the DVOR shelter still uses a conventional mechanical key and nothing can be used for the DVOR equipment from the technician's room. If someone is missing or there is nothing good and unknown to the technicians being discussed. In this case the author designed a DVOR shelter safety system using the keypad, password, IP camera, and Raspberry Pi in LPPNPI Yogyakarta Branch Office which still uses the key as access to DVOR shelter and the unavailability of equipment for DVOR. With that, they can support the activities of flight navigation services